Henry IV : Part 1 - Shakespeare, William, 1564-1616 (New York Simon & Schuster Paperbacks, 2011)
Powerful rebels are mustering their forces to topple the aging King Henry IV from his throne. Their success seems assured because the dying king cannot depend upon his son and heir Prince Hal. Instead, King Henry relies on the aid of the latest war hero Sir John Falstaff ... and the kingdom is soon in for a big surprise.
Incude Illustrations
Keywords: Henry IV, King of England, 1367-1413 -- Literature -- Shakespeare, William, 1564-1616 -- English Drama--Early Modern and Elizabethan